2002
DOI: 10.1002/ajhb.10093
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity associated with poor sleep quality in adolescents?

Abstract: Obesity has reached epidemic proportions in the U.S. and more developed countries, particularly so among adolescents. A substantial impact on public health could be achieved if other factors causing obesity besides the conventional ones of diet and physical activity could be identified and acted upon. The present study investigates whether there is a link between low sleep quality and obesity in a tri-ethnic, cross-sectional sample (n = 383) of male and female adolescents ages 11-16 years old (Heartfelt Study)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
266
4
13

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(300 citation statements)
references
References 32 publications
17
266
4
13
Order By: Relevance
“…In addition, our study suggests that adolescents who sleep enough hours at night according to the public health recommendation for these ages (12) are likely to commute actively to school. Several previous studies that examined the associations between sleep duration and daily physical activity in adolescents reported contradictory findings and, overall, did not support a plausible cause-and-effect relationship (17)(18)(19) . Morning fatigue may mediate our significant association between sleep duration and active commuting to school (19) .…”
Section: Discussionmentioning
confidence: 81%
“…In addition, our study suggests that adolescents who sleep enough hours at night according to the public health recommendation for these ages (12) are likely to commute actively to school. Several previous studies that examined the associations between sleep duration and daily physical activity in adolescents reported contradictory findings and, overall, did not support a plausible cause-and-effect relationship (17)(18)(19) . Morning fatigue may mediate our significant association between sleep duration and active commuting to school (19) .…”
Section: Discussionmentioning
confidence: 81%
“…In these studies, differences between time spent in bed and effective sleep duration are difficult to ascertain. Only a few studies have relied on objective methods such as accelerometry (Kramer et al, 1999;Gupta et al, 2002). In the present study, it was not possible to use questionnaires or diaries for practical reasons (the girls did not have a precise knowledge of time) and direct observation of behaviour implied an unacceptable intrusion into the adolescents' privacy.…”
Section: Discussionmentioning
confidence: 89%
“…Most of our knowledge of the topic stems from research carried out in industrialized countries. In those studies, the importance of sleep as a component of daily energy expenditure was seldom considered, apart from its relation to obesity (Gupta et al, 2002) or sports participation (Ribeyre et al, 2000). However, in a developing country like Senegal where food insecurity is widespread, and dietary intakes insufficient at certain periods (Simondon et al, 1993), sleep and rest may act as a buffer mechanism to spare energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 The most probable sleep factor linked with obesity is sleep duration. Cross-sectional evidence suggests an association between short sleep and obesity in children [8][9][10][11] and in young adults. [12][13][14][15] In addition, two prospective cohort studies have shown that short sleep predicts future weight gain in young adults 16 and in middle-aged women.…”
Section: Introductionmentioning
confidence: 99%